2016
DOI: 10.11005/jbm.2016.23.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Serum Sclerostin Levels in Patients with Human Immunodeficiency Virus Infection and Their Association with Bone Turnover Markers and Bone Mineral Densitometry

Abstract: BackgroundThe aim of the study was to compare serum sclerostin levels in human im-munodeficiency virus (HIV)-infected patients and healthy controls, and to evaluate their relationship with bone turnover markers (BTM) and bone mineral density (BMD).MethodsWe prospectively studied 33 HIV treatment-naive patients and 63 healthy individuals; matched for age and sex. Serum sclerostin levels, BTM, BMD were measured. Viral load and cluster of differentiation 4 (CD4) levels were also assessed in HIV-infected patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
4
1
Order By: Relevance
“…In contrast, BMI and SAT were not associated with frailty. Although HIV was associated with increased frailty, the effect of these body composition measurements on frailty did not differ by HIV serostatus [35, 31, 32]. In contrast to prior studies linking frailty to low CD4 count and a history of AIDS [8, 33, 34], we did not find an association between frailty and HIV-specific factors, likely reflective of low rates of clinical AIDS and high CD4 T-cell counts.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, BMI and SAT were not associated with frailty. Although HIV was associated with increased frailty, the effect of these body composition measurements on frailty did not differ by HIV serostatus [35, 31, 32]. In contrast to prior studies linking frailty to low CD4 count and a history of AIDS [8, 33, 34], we did not find an association between frailty and HIV-specific factors, likely reflective of low rates of clinical AIDS and high CD4 T-cell counts.…”
Section: Discussioncontrasting
confidence: 99%
“…A previous study in therapy-naïve primary HIV-infected (PHI) men, showed that bone turnover did not differ between those with a normal or a reduced BMD [ 10 ]. However, most other studies show higher BTMs in PHI-men [ 3 , 4 , 6 , 10 , 22 24 ]. These heterogeneous data might be caused by the choice of BTM, pre-analytical differences (for instance time of the blood withdrawal, fasting sample or not), the applicable reference interval of the BTM, or differences in patient characteristics (for instance males versus females).…”
Section: Introductionmentioning
confidence: 85%
“…The hip BMD decreased less in the untreated group compared to the treated group. Several underlying mechanisms could result in the further decrease of BMD such as persistent vitamin D deficiency, continued immune activation and cytokine release induced by the HIV-infection itself, and cART effects in the treated group [ 6 , 10 , 12 , 20 , 23 , 26 , 28 , 31 ]. Currently, the European HIV guidelines indicate to screen only persons who are at risk for vitamin D deficiency and not all PHI-patients [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serum sclerostin levels were significantly reduced in HIV-infected patients compared to healthy controls. It has been suggested that untreated HIV and/or systemic inflammation may be a major regulator of serum sclerostin [19]. Different results were obtained in HCV, another viral disease.…”
Section: Discussionmentioning
confidence: 99%